Hi guys. Basically as the title says can someone guide me through the problem of...
Make x the subject of
5(x-3) = y(4-3x)
Thanks any help and guidance would be greatly appreciated.
Hi guys. Basically as the title says can someone guide me through the problem of...
Make x the subject of
5(x-3) = y(4-3x)
Thanks any help and guidance would be greatly appreciated.
Hi MattA147.
The question being begged is: 'How do you solve this problem explicitly for x'.
Changing the subject of a formula basically means that if you have a formula in the form: $\displaystyle y=x+3$ then the 'subject' of the formula is 'y'. Changing the subject to 'x' would yield: $\displaystyle x=y-3$.
So in your problem we have: $\displaystyle 5(x-3)=y(4-3x)$ and we want to make 'x' the subject of the formula.
Let's start by getting rid of those parentheses:
$\displaystyle 5(x-3)=y(4-3x)\\ \Rightarrow\\5x-15=4y-3yx$
Now let's solve for 'x':
$\displaystyle 5x-15=4y-3yx\\ \Rightarrow\\5x+3yx=15+4y\\ \Rightarrow\\x(5+3y)=15+4y\\ \Rightarrow\\x=\frac{4y+15}{3y+5}$